Microarray Gene Expression Profiling of Angiogenesis Inhibitors Using the Rat Aortic Ring Assay. (September 2002) - Zogakis, T.G.; Costouros, N.G.; Kruger, E.A.; Forbes, S.; He, M.; Qian, M.; Feldman, A.L.; Figg, W.D.; Alexander, H.R.; Liu, E.T.; Kohn, E.C.; Libutti, S.K.
The rat aortic ring assay has been previously described as a useful ex vivo model for analyzing the biological activity of various inhibitors of angiogenesis. Rat aortic rings are exposed to antiangiogenic agents for a five-day incubation period. Then, the degree of microvessel outgrowth from the rings is analyzed and quantified. In contrast to most in vitro angiogenesis assays, the rat aortic ring model provides a unique microenvironment to evaluate the interaction of various cell types and biological factors for their influence on angiogenesis. Microarray analysis is an accepted method for the evaluation of gene expression profiles and can be used to better understand changes in gene expression that occur when rat aortic rings are exposed to a particular biological agent. Here we describe a method of using microarray technology to evaluate the modulation of gene expression in angiogenesis using the rat aortic ring assay.